2011
DOI: 10.1007/s12160-011-9262-4
|View full text |Cite
|
Sign up to set email alerts
|

Children with Diabetes Compared to Peers: Depressed? Distressed?

Abstract: Background It is not clear from the literature whether children with diabetes have more psychological difficulties than their peers. Purpose This study aims to use meta-analysis to determine if children with diabetes differ from children without a chronic illness in a variety of domains reflecting psychological well-being. Method A meta-analysis was undertaken of 22 studies that compared children with diabetes to a comparison group. Outcomes included depression, anxiety, behavioral problems, and related co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
143
2
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(168 citation statements)
references
References 53 publications
12
143
2
11
Order By: Relevance
“…65 Moreover, among young adult males in 2 Finnish population samples, severity of depressive symptoms was associated with insulin resistance. 66,67 In meta-analytic findings, depressive symptoms along with other psychological symptoms were more common among children with versus without T2DM, 68 and there was preliminary evidence that the association between depression and T2DM was especially strong in youth. 69 There is pharmacoepidemiological evidence of elevated rates of hyperglycemia and †"Youth" is used in this statement as an umbrella term for children, adolescents, and/or young adults (defined here as mean sample age within 1 standard deviation of 30 years).…”
Section: Insulin Resistance and Diabetes Mellitus (T2dm)mentioning
confidence: 99%
“…65 Moreover, among young adult males in 2 Finnish population samples, severity of depressive symptoms was associated with insulin resistance. 66,67 In meta-analytic findings, depressive symptoms along with other psychological symptoms were more common among children with versus without T2DM, 68 and there was preliminary evidence that the association between depression and T2DM was especially strong in youth. 69 There is pharmacoepidemiological evidence of elevated rates of hyperglycemia and †"Youth" is used in this statement as an umbrella term for children, adolescents, and/or young adults (defined here as mean sample age within 1 standard deviation of 30 years).…”
Section: Insulin Resistance and Diabetes Mellitus (T2dm)mentioning
confidence: 99%
“…367 A meta-analysis of 22 case-control studies found that psychological problems, including depressive symptoms, were more likely among children with versus without diabetes mellitus, 368 although exceptions exist. 369,370 In a large study of youth with T1DM, 17% had significant depressive symptoms, half of whom did not discuss these symptoms with their pediatrician or nurse.…”
Section: Depressionmentioning
confidence: 99%
“…A meta-analytic report, which included 22 studies, indicated that children suffering from DM, compared to peers, experience elevated levels of depression, anxiety and psychological distress, although the effect was found to be small to medium 18 . Furthermore, it showed that children with poor metabolic control amongst DM patients manifest larger anxiety and psychosocial distress, meaning that poorer control of the disease could lead to mental problems 18 . Another systematic review and meta-analysis 19 , which included 14 studies, showed that the occurrence of anxiety symptoms is raising up to every third child and adolescent suffering from T1D.…”
Section: Prevalence Rates Of Anxiety and Depressive Symptoms In Dmmentioning
confidence: 99%
“…Nevertheless, even if DM is shown to be a risk factor for depression onset 18 , the relationship could be bidirectional, since it is possible for mental health problems to also cause poorer metabolic control 22,23 . A few authors state that DM is not a risk factor for depression, although it can strengthen the severity of psychological symptoms 19 .…”
Section: Dm As a Stressful Life Experiencementioning
confidence: 99%